REPURPOSING DONEPEZIL AS A POTENTIAL ZIKA VIRUS INHIBITOR: A SYSTEMATIC VIRTUAL SCREENING AND MOLECULAR DOCKING APPROACH - FRIDAY, AMAKU JAMES; MAGAJI, BUHARI; ONYEKACHI, TOBBY CASSANDRA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
A potential global threat of Zika virus (ZKV) as observed in February 2016 in Brazil has called for intensive surveillance and proactive measures to ensure its spread and re-emergence are nipped. However, clinically approved drugs for dengue have shown insufficient capacity in curbing ZKV. Hence, a systematic repurposing of drug with alien therapeutic implication via the ligand-based virtual screening approach may proffer a path to finding drugs with potential to inhibit ZKV. Compounds retrieved from the ZINC database were docked with 5Y6N protein by making use of AutoDockVina tools. In silico prediction of pharmacokinetic properties and quantum chemical calculations of The best hit were assessed. The best five drug-like compounds were identified and among these five compounds, ZINC84071344 (N-(2-fluoro-5-nitrophenyl)-6- methoxypicolinamide) was found to interact best with 5Y6N protein with a binding energy of – 6.6 kcal/mol and the formation of H-bonds with LYS 200, GLY 199 and ARG 462 amino acid residues. The lead molecule (ZINC84071344) exhibit the tendency to possess high physicochemical and ADME properties for an oral drug. A further experimental assessment of ZINC84071344 could lead to the discovery of novel inhibitor of 5Y6N protein.